REFORMIS DALAM HADITS NABI - Asyhar - Kholil (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2019)
Assunnah is a source of law in Islam, Sunnah itself contains the words, deeds, and statutes of the Prophet Muhammad pbuh. Indeed Assunnah now faces several challenges in large scale. Someone is called a reformer if the entire activity is in the interests of the Muslims, which can be felt by all the Muslims. A reformer in Islam urgently needed, therefore God has created mankind can figure out the problem and the solution, each end of the century